ANALISIS TINGKAT STRES DENGAN EVALUASI PENGOBATAN AKHIR TUBERKULOSIS - Juati; Joko Sapto Pramono; Tini (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
ABSTRACT The treatment period for patients with tuberculosis (TB) in the intensive and advanced stages is 6-9 months, the long treatment time and close supervision cause psychological stress which can have an impact on treatment outcomes. This study aims to determine the relationship between stress levels and the treatment outcomes of TB patients at RSUD dr. H Soemarno Sosroatmodjo Tanjung Selor, North Kalimantan Province. The design of this research is descriptive correlation with cross sectional approach. Samples were taken as a total sampling of 50 patients diagnosed with tuberculosis and currently undergoing treatment. The statistical test used is the chi square and alternative Kolmogorov-Smirnov test. The results of the study showed that the value of p = 0.00 was less than the value of ? = 0.05, which means that there is a relationship between stress levels and the results of pulmonary TB treatment at RSUD dr. H. Soemarno Sosroatmodjo Tanjung Selor, Tanjung Selor. Conclusion: the long period of treatment for pulmonary TB causes stress in patients as evidenced by the results of research that has a significant relationship between stress levels and the results of pulmonary TB treatment. It is recommended that health workers provide more intensive motivation and assistance so that treatment can be completed without causing stress. Keywords: Treatment evaluation; stress; tuberculosis. ABSTRAK Masa pengobatan penderita tuberculosis (TB) tahap intensif dan lanjutan selama 6 – 9 bulan, waktu pengobatan yang cukup lama dan pengawasan yang ketat menimbulkan stres psikologis yang dapat berdampak pada evaluasi pengobatan. Penelitian ini bertujuan untuk mengetahui hubungan tingkat stres dengan evaluasi pengobatan pasien TB di RSUD dr. H Soemarno Sosroatmodjo, Tanjung Selor, Provinsi Kalimantan Utara. Desain penelitian ini adalah deskriptif korelasional dengan pendekatan cross sectional. Sampel diambil secara total sampling sebanyak 50 pasien yang terdiagnosis tuberculosis dan sedang menjalani pengobatan. Uji statistik yang digunakan adalah chi square dan alternatif uji Kolmogorov-Smirnov. Hasil penelitian didapatkan nilai p = 0,00 lebih kecil dari nilai ?= 0,05 yang berarti terdapat hubungan antara tingkat stres dengan evaluasi pengobatan TB Paru di RSUD dr. H. Soemarno Tanjung Selor. Kesimpulan: lamanya masa pengobatan TB paru menimbulkan stress pada pasien terbukti dari hasil penelitian yang signifikan hubungan antara tingkat stres dengan evaluasi pengobatan TB Paru. Disarankan kepada tenaga Kesehatan memberikan motivasi dan pendampingan yang lebih intensif agar pengobatan selesai tanpa menimbulkan sress. Kata kunci: Evaluasi pengobatan; stres; tuberculosis.